2014
DOI: 10.3109/0886022x.2014.880325
|View full text |Cite
|
Sign up to set email alerts
|

False positivity of gamma-glutamyl transpeptidase measurement in urine

Abstract: Although enzymuria tends to be associated to renal injury, there are no studies that have evaluated the presence of the enzyme gamma-glutamyl transpeptidase (GGT) spectrophotometry in the urine using a non-nephrotoxic agent (Nerium oleander) in order to evaluate the possibility of false positive results. The urinary GGT/urinary creatinine concentration ratio (uGGT/uCr) of 10 healthy dogs was calculated and posteriorly confronted with data from clinical evaluation, hematological and serum biochemical profiles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
6
0
3
Order By: Relevance
“…Furthermore, induction of muscular inflammation with injection of Freund's complete adjuvant resulted in decreased uGGT/c in horses, and it was suggested that the presence of inflammation may affect the reliability of uGGT/c as an index of renal damage . One study reported that uGGT/c was increased after the administration of a nonnephrotoxic agent in dogs and concluded that this reflected false positive results . However, mild tubular damage might still have been missed on ultrastructural examination given the tendency for such lesions to be focally distributed.…”
Section: Renal Biomarkers: Urinementioning
confidence: 99%
“…Furthermore, induction of muscular inflammation with injection of Freund's complete adjuvant resulted in decreased uGGT/c in horses, and it was suggested that the presence of inflammation may affect the reliability of uGGT/c as an index of renal damage . One study reported that uGGT/c was increased after the administration of a nonnephrotoxic agent in dogs and concluded that this reflected false positive results . However, mild tubular damage might still have been missed on ultrastructural examination given the tendency for such lesions to be focally distributed.…”
Section: Renal Biomarkers: Urinementioning
confidence: 99%
“…Em pequenas concentrações, pode ser encontrado em outros órgãos como fígado, pâncreas, baço, pulmões, intestino delgado, placenta, sistema nervoso central, próstata e coração (RUDOLPH e CORVALAN, 1992). A espectrofotometria é o método mais utilizado para sua dosagem urinária, porém outras técnicas também são descritas (CRIVELLENTI et al 2014).…”
Section: Gama Glutamiltransferase Urinária (Ggt Urinária)unclassified
“…Em contrapartida Crivellenti et al (2014) demonstram que aumento da GGT urinária pode não estar necessáriamente relacionada as alterações histopatológica dos rins em casos de intoxicação por substâncias não nefrotóxicas.…”
Section: Gama Glutamiltransferase Urinária (Ggt Urinária)unclassified
See 1 more Smart Citation
“…Reported disorders associated with increased values of uGGT are shown in Table 1. Urinary GGT activity has great potential in safety assessment studies (Narita et al 2007;Borges et al 2013) Nevertheless, Crivellenti et al (2014) reported false positive results of urinary GGT measurement in dogs poisoned by a non-nephrotoxic agent (Nerium oleander).…”
Section: Gamma-glutamyl Transpeptidasementioning
confidence: 99%